Analysis of Communication Skill 5th-Grade Students on Fire Materials Through RADEC Learning - Ika Rosmiati; Atep Sujana; Wahyu Sopandi; Roni Wahyu Wandani (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2023)
Communication skills in science learning need to be developed. This is because through communication students can organize their thinking. The purpose of this study was to determine the communication skills of elementary school students through the RADEC learning model. This research was conducted using a qualitative approach with a qualitative descriptive design. The subjects of this study were 18 fifth-grade students at one of the public elementary schools in the city of Bandung. Data on science communication skills were obtained through questionnaires and documentation and analyzed descriptively using percentage calculations. The results showed that the student's communication skills belonged to the visible category. The highest percentage on the indicators of clarity of speech and choice of words is 88%, while the lowest percentage is on the indicator of using library sources (printed books, internet, newspapers or magazines, TV, radio, etc.) according to the material being studied, which is 59%. The RADEC learning model has a good influence, especially on the discussion process . Keywords: Communication Skills, RADEC Learning, Fire.